RUINS NARRATE THE HISTORY OF THE ISLET OF AGIOS GEORGIOS IN SALAMIS THROUH A CULTURE ROUTE - Delazanou, Maria Athanasios (Design/Arts/Culture, 2022)
This paper deals with ruins and deliberate abandonment, through the “experience” of a cultural route that will bring back memories from the dark pages of history, where “mourning” awakens social consciences so that, future generations can have a better future. The research took place in the islet of Agios Georgios, in historic Salamis. Rich photographic material captures a haunted landscape that through its endless silence, the echo of the wilderness is heard, whispering towards Perama and Paloukia, unknown stories of people who lived, were abandoned and left their last breath there. The proposed cultural route consists of nine thematic stops, which narrate the daily routine in a lazaretto quarantine island. Each stop connects the ruins with their past. Each building illustrates traumatic memories contributing to an interpretation of our history, highlighting and raising awareness of the character of this dark heritage. The ultimate goal and vision of this cultural route is to be included in the tourist map of Greece, inspiring respect, not only for the martyrdom events but also for the natural and architectural landscape of the islet of Agios Georgios.